Supporting Sustainability through Maritime Literacy and Valuable Reflections for the Future: A Systematic Literature Review - Husamah, Husamah; Rahardjanto, Abdulkadir; Lestari, Nurdiyah; Permana, Tutut Indria; Hadi, Samsun (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study investigates Scopus-indexed articles to identify literacy trends that support maritime sustainability and derive key insights for future research and development. Using a PRISMA-based systematic literature review (SLR) combined with thematic analysis, the findings reveal an increasing trend in publications, primarily in the fields of environmental sciences, social sciences, and biology. Highly cited works, such as those by Kelly et al. and Gutierrez and Thornton, highlight dominant research contributions from the United States, the United Kingdom, and the European Union, with the European Union emerging as a key funding source. Six interrelated keywords were identified: sustainability, literacy, education, students, knowledge, and Sustainable Development Goals (SDGs). The review identifies five critical themes: marine sustainability and literacy, education, collaboration and stakeholder engagement, challenges and opportunities in marine resource management, and social awareness. In conclusion, the study underscores the growing importance of publications on maritime sustainability, driven by international collaborations and thematic focus on six central keywords.